Taking over of religious charity foundations in the People’s Republic of Poland before the decree of 24th April 1952 on abolition of foundations entered into life - Szymański, Andrzej (The Opole Studies in Administration and Law, 2017)
This article analyses, in terms of the legal aspect, the process of dissolution of selected religious foundations before the decree of 24th April 1952 concerning the elimination of those foundations entered into life. The author bases his arguments on the analysis of concrete cases, whose descriptions were found during his archival research.